1995
DOI: 10.1093/infdis/172.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunization with Recombinant Helicobacter pylori Urease Induces Secretory IgA Antibodies and Protects Mice from Challenge with Helicobacter felis

Abstract: Helicobacter pylori, a gram-negative spiral bacterium, is the cause of chronic superficial (type B) gastritis and peptic ulcer disease. The urease enzyme of H. pylori was expressed as an inactive recombinant protein in Escherichia coli, purified as particulate structures of 550-600 kDa molecular mass with a diameter of approximately 12 nm. Given orally, 5 micrograms of urease with an appropriate mucosal adjuvant, such as the labile toxin of E. coli, protected 60%-100% of mice against challenge with virulent He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(194 citation statements)
references
References 50 publications
8
181
1
3
Order By: Relevance
“…Previous reports document successful protection against infection by Helicobacter felis in mice, using the following orally administered combinations: H. felis antigen plus adjuvant cholera toxin as well as the nontoxic cholera toxin B subunit (Lee, A. & Chen, 1994); recombinant H. pylori GroES-like heat shock proteins in combination with the B subunit of H. pylori urease (Ferrero et al, 1995); and recombinant H. pylori urease with adjuvant E. coli toxin (Lee, C. K. et al, 1995). Currently it is not known whether a similar protection against H. pylori infection of adequate duration can be achieved in humans.…”
Section: • Vaccine Prospectsmentioning
confidence: 99%
“…Previous reports document successful protection against infection by Helicobacter felis in mice, using the following orally administered combinations: H. felis antigen plus adjuvant cholera toxin as well as the nontoxic cholera toxin B subunit (Lee, A. & Chen, 1994); recombinant H. pylori GroES-like heat shock proteins in combination with the B subunit of H. pylori urease (Ferrero et al, 1995); and recombinant H. pylori urease with adjuvant E. coli toxin (Lee, C. K. et al, 1995). Currently it is not known whether a similar protection against H. pylori infection of adequate duration can be achieved in humans.…”
Section: • Vaccine Prospectsmentioning
confidence: 99%
“…Both these results lead to the conclusion that mucosal IgA level might be protecting the mucosa by lowering the bacterial density. Studies have suggested that locally produced antibodies, particularly IgA [13,14], might block H. pylori infection by preventing colonization and adhesion and allowing killing by neutrophils or monocytes through bacterial opsonisation [15,16]. Helicobacter-specific IgA monoclonal antibodies administered directly into the gastric lumen conferred protection against H. felis infection [11,17] and neutralized the toxic products of Helicobactor pylori [18].…”
Section: Discussionmentioning
confidence: 99%
“…Representative examples include the tetanus toxoid (Xu-Amano et al, 1993), (Yamamoto et al, 1996), (Cheng et al, 1999), (Xu-Amano et al, 1994), the inactivated influenza virus (Hashigucci et al, 1996), (Tumpey et al, 2001), a recombinant urease from Helicobacter spp. (Lee et al, 1995), (Weltzin et al, 1997), (Lee, 2001), and the pneumococcal surface protein A from S. pneumoniae (Wu et al,1997). Many other examples have been reported, and all these studies clearly indicate that both LT and CT have significant potential for use as adjuvants for mucosally administered antigens.…”
Section: Vaccinesmentioning
confidence: 91%